2014
DOI: 10.1007/s10654-014-9950-z
|View full text |Cite
|
Sign up to set email alerts
|

Obesity measures and risk of venous thromboembolism and myocardial infarction

Abstract: Obesity is a risk factor for arterial and venous thromboembolism. However, it is not known whether obesity mediates risk through shared mechanisms. In a population-based cohort, we aimed to compare the impact of obesity measures on risk of venous thromboembolism (VTE) and myocardial infarction (MI), and explore how obesity-related atherosclerotic risk factors influenced these relationships. Measures of body composition including body mass index , waist circumference (WC), hip circumference (HC), waist-hip rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 59 publications
1
41
1
1
Order By: Relevance
“…We previously reported an association of higher waist circumference with VT in a study focused on metabolic syndrome and VT risk[24]. In the Tromso study, among different measures of body size, the top quintile of waist circumference showed the highest risk estimates for VT; HR 3.6 in men and 2.3 in women [25]. The highest RR in the current study was for BMI in the top quartile, RR 3.0.…”
Section: Discussionmentioning
confidence: 46%
“…We previously reported an association of higher waist circumference with VT in a study focused on metabolic syndrome and VT risk[24]. In the Tromso study, among different measures of body size, the top quintile of waist circumference showed the highest risk estimates for VT; HR 3.6 in men and 2.3 in women [25]. The highest RR in the current study was for BMI in the top quartile, RR 3.0.…”
Section: Discussionmentioning
confidence: 46%
“…45,7476 Horvei and colleagues reported that waist-to-hip ratios and waist-to-height ratios had the greatest risk for AMI in women who participated in the Tromso Study (1994–1995) and were evaluated up to 2011. 77 In another study in patients with IHD and hypertension, the majority of obese individuals were women (67.1%) and they had a higher prevalence of diabetes, dyslipidemia, and left ventricular hypertrophy and heart failure than normal weight women. 78 In addition, hypertension was only controlled in less than 35% of obese individuals, compared to 52% in normal weight individuals, and diabetes was controlled in only 18% of obese individuals compared to 43% in normal weight individuals.…”
Section: How Women Experience Ischemic Heart Diseasementioning
confidence: 97%
“…11 Obesity is a dose-dependent risk factor for VTE with an estimated hazard ratio of 1.07 per standard deviation or 2.14 for obese versus normal weight women. 12, 13 Current smoking confers a relatively small increase in risk for VTE, with a relative risk of 1.23 in a recent meta-analysis. 26 Age is also a strong risk factor for VTE.…”
Section: Introductionmentioning
confidence: 99%